Pemikiran Politik Tan Malaka Tentang Konsep Negara Indonesia - Ponirin Ponirin; Agum Patria Silaban (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2019)
It aims to test anything that influences the Political thinking Tan Malaka about the Consept of the Indonesian State, setting aside the concept of the state in the view of Tan Malaka and putting forth the effort the makes in fulfilling the concept of a joyful state. This type of research is a study literature. As for data collection techniques in this study is a library study, it means the author did reseach by collecting books, documents, articles, scripts, and the like. With the approach: textual studies, context studies, and historical studies. The data analysis of the data is heuristic, criticism, interpretation, and presentation. From the results of the research, it is known that Tan Malaka was a hero of the independence movement, he was born in the village of Pandan Gadang, not far from the Suliki Sprout, Limopilih Koto Regency, East Sumatera. He began to think of the fate of this people who were colonized after education in the Netherlands. The influence of circumstances and understanding is like the circumstances of his people, then education that this finally influenced by Marxism and the revolutiomary movement of Europe (the French, British, and Russian Revolutions) have set the mind to a left (Communist). Long before the other leading figures of independence, Tan Malaka had designed the consep of the Indonesian state before the independent of Indonesia. He saw and compared the concept of repulic and kingdom. For him the kingdom is irrelevant to the welfare of the people. Tan Malaka would prefer the concept of a union or a republic with a democratic system. For him the people must be in charge.then it may be concluded tha the concept of the Indonesian state tha Tan Malakan was the DemocraticKey word : Tan Malaka's Point of view, Indonesian State